Strategi Pemasaran Pada UMKM Di Sirah Kencong Melalui Pembuatan Banner - Nurul Lailis Shofi; Ika Korika Swasti (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
By considering the various issues affecting Micro, Small and Medium Enterprises (MSMEs) in Sirah Kencong, guidance is needed to help MSMEs design effective marketing strategies and expand their market coverage. To deal with this problem, a method is used, namely the implementation method. This implementation method includes several things including a survey of MSMEs, design planning, material selection and determining the size of the banner to be used. The results of this service show that these MSMEs need branding in the form of making banners. The banner creation stage begins with this stage, namely designing banners for Micro, Small and Medium Enterprises (MSMEs) aimed at increasing visibility and promoting products, conveying information about MSMEs. Designed to reinforce brand identity by highlighting consistent visual elements, encouraging active responses from customers. After designing the banner design, the next step is to print the banner to the agreed size. The MSME owner has approved the size and material of the banner. In this way, the resulting banner will be in accordance with your wishes and approval. Next, this is the final stage after going through the printing process, the banner is handed over to the MSME owner. After handover, the next step is to install the banner in the location or area that has previously been decided with the MSME owner. The purpose of this installation is to increase the visibility of the banner and maximize the marketing impact, so that more people can see and respond to the information or promotions conveyed through the banner.